1990
DOI: 10.1038/343482a0
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of the synthesis of edited and unedited COIII RNA in Trypanosoma brucei

Abstract: RNA editing, a novel and unexpected type of information processing, was first demonstrated in the kinetoplasts of certain protozoans. It is a remarkable phenomenon: certain species of messenger RNA have nucleotide sequences that differ greatly from the sequences of the genes from which they are presumably transcribed. The differences are usually due to addition of uridylate residues, but occasionally also to their deletion. The most spectacular case of editing known occurs in the mRNA of the mitochondrial gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Thus, all queries for the presence of SL in organellar transcripts were negative (SI Table 1). Similarly, no product was obtained in PCRs that used DinoSL and small subunit ribosomal RNA (18S rRNA)-specific primer sets for cDNA synthesized with random hexamers, indicating that SL is not added to 18S rRNA, a result consistent with previous reports that SL is not present at the 5Ј end of the transcripts of 5.8S rRNA (i.e., RNA pol I) (21), 5S rRNA (i.e., RNA pol III) (22), or mitochondrial mRNAs in Trypanosoma brucei (23), although trans-splicing of the geneinternal variety occurs in mitochondrial genes of some organisms (24). The presence of SL on nuclear-encoded mRNAs of proteins destined for organellar import supports the hypothesis that transsplicing is generally required for nuclear gene expression; alternatively, adoption of the trans-splicing pathway may have allowed an easier transition for gene relocation into the nuclear genome.…”
Section: Sl Addition Is Common In Dinoflagellate Mrnasupporting
confidence: 77%
“…Thus, all queries for the presence of SL in organellar transcripts were negative (SI Table 1). Similarly, no product was obtained in PCRs that used DinoSL and small subunit ribosomal RNA (18S rRNA)-specific primer sets for cDNA synthesized with random hexamers, indicating that SL is not added to 18S rRNA, a result consistent with previous reports that SL is not present at the 5Ј end of the transcripts of 5.8S rRNA (i.e., RNA pol I) (21), 5S rRNA (i.e., RNA pol III) (22), or mitochondrial mRNAs in Trypanosoma brucei (23), although trans-splicing of the geneinternal variety occurs in mitochondrial genes of some organisms (24). The presence of SL on nuclear-encoded mRNAs of proteins destined for organellar import supports the hypothesis that transsplicing is generally required for nuclear gene expression; alternatively, adoption of the trans-splicing pathway may have allowed an easier transition for gene relocation into the nuclear genome.…”
Section: Sl Addition Is Common In Dinoflagellate Mrnasupporting
confidence: 77%
“…On the other hand, the complementarity of positive-and negative-strand COIII RNA, including their termini, and the complementary disposition of edited regions in partially edited positive-and negative-strand RNA molecules suggest a template-product relationship between positive-and negative-strand RNA. This structural relationship, taken together with the demonstration that a significant proportion of edited COIII RNA is synthesized as a unit (10) and the identification of an RNA-dependent RNA polymerase activity in extracts of T. brucei (V.V., B.S., and S.R., unpublished results), is consistent with the function of negative-strand RNA as an intermediate template in RNAdependent RNA synthesis. Such a process, which seems to have no obvious relationship to the process of RNA editing, may play an important role in RNA metabolism in T. brucei as a mechanism of RNA amplification.…”
Section: Methodssupporting
confidence: 49%
“…In the course of studies of RNA editing, we observed that a significant proportion of some edited mRNA species in Trypanosoma brucei is the product of an actinomycin D-resistant (i.e., presumably DNA-independent) transcriptional process (10). This finding suggested the occurrence in T.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…For gel analysis, RNA samples (30 ,ug) were denatured (3 min at 100°C in 1 mM EDTA, pH 6.2), resolved in 1.5% agarose/formaldehyde gels, blotted to nitrocellulose, and hybridized with 5'-end-labeled oligonucleotides specific for either sense (probe 1) or antisense (probe 2) globin RNA as described (7). The blot hybridized with sense strand-specific probe was exposed for 45 min, whereas the blot hybridized with antisense strand-specific probe was exposed for 3 days.…”
Section: Methodsmentioning
confidence: 99%